2001
DOI: 10.1021/bi002670n
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the RANTES-Glycosaminoglycans Interactions

Abstract: Chemokines mediate their biological activity through activation of G protein coupled receptors, but most chemokines, including RANTES, are also able to bind glycosaminoglycans (GAGs). Here, we have investigated, by site-directed mutagenesis and chemical acetylation, the role of RANTES basic residues in the interaction with GAGs using surface plasmon resonance kinetic analysis. Our results indicate that (i) RANTES exhibited selectivity in GAGs binding with highest affinity (K(d) = 32.1 nM) for heparin, (ii) RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 47 publications
10
127
1
Order By: Relevance
“…It is well-established that CCL5 mediates its biological activities through activation of the G-protein-coupled receptors CCR1, CCR3, and CCR5 [49]. We observed expression of all the CCL5 receptors (CCR1, CCR3, and CCR5) in ovarian CSLCs.…”
Section: Cslcs and Cd133mentioning
confidence: 55%
“…It is well-established that CCL5 mediates its biological activities through activation of the G-protein-coupled receptors CCR1, CCR3, and CCR5 [49]. We observed expression of all the CCL5 receptors (CCR1, CCR3, and CCR5) in ovarian CSLCs.…”
Section: Cslcs and Cd133mentioning
confidence: 55%
“…A dual role of chemerin cannot therefore be excluded, and specific actions of the cystatin-like module are presently being analyzed. The N-terminal domain of chemerin might also interact with proteoglycans, similarly to the core domain of chemokines, and this property could be essential for promoting leukocyte migration in vivo (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Residues Arg-47 and Arg-17 of CCL5 have been shown to play a crucial role in the CCL5-CCR1 binding event (29,30), and the N terminus of CCL5 is known to be crucial for CCR1 signaling (30,31). Although it has previously been shown that pools of heparin-derived oligosaccharides can inhibit the binding of CCL5 to its receptor, CCR1 (29), no specific sulfation pattern or motif is known to be optimal for binding to CCL5. GAG heterogeneity makes such evaluations particularly challenging and presents a role for computational methods to provide theoretical insights.…”
Section: Rknrmentioning
confidence: 99%
“…Residues Arg-47 and -17 of CCL5 are known to play a crucial role in the CCL5-CCR1 binding event (29,30), whereas the N terminus of CCL5 is crucial for CCR1 signaling (30,31). Based on the per-residue MM-GBSA data, each ligand interacts with these residues to varying degrees.…”
Section: Volume 290 • Number 25 • June 19 2015mentioning
confidence: 99%